Cultural heritage of the village of Pokój (former Carlsruhe) in the Opole Province Disappearance, protection, promotion - Adamska, Monika Ewa (Przestrzenny wymiar badań dziedzictwa kulturowego: Studia z Geografii Politycznej i Historycznej 2020. T. 9-10, 2021)
Pokój is a communal village located in the northern part of the Opole Province. In the 18th century Duke Karl Christian Erdmann of Württemberg-Oels erected a residential complex here in the form of a radial composition with a central square, gardens and parks. The place known as Carlsruhe became a cultural and craft center, as well as a recognized health resort since the 19th century. War damage suffered by the village in 1945 interrupted this development. The former Carlsruhe became a village Pokój. This chapter presents activities and projects implemented towards protection and promotion of preserved cultural heritage of Pokój at the background of the place’s history and its cultural specificity. The study shows, that after the period of post-war stagnation and degradation, 21st century brings a series of new opportunities and instruments not only for protection of the unique heritage of Pokój and restoration of its former values, but for sustainable use of this heritage for local and regional development as well.